APPLICATIONS OF DRONE TECHNOLOGY IN CONSTRUCTION PROJECTS: A SYSTEMATIC LITERATURE REVIEW - Siju, Nitha Mary; Shafiyia, Syeeda; Ben Maaouia, Maroua (International Journal of Research -GRANTHAALAYAH, 2022)
Drone technology has evaded various sectors, among which Construction is a prominent one. The communication between stakeholders can be improved using Drone technology. Furthermore, the use of drone technology will help them to accomplish the project on time and on budget. This paper aims to study the potential of the utilization of drones in the construction industry and extend it to understand the benefits and impacts of drones as a new trend. This is a review article based on SPAR4 SLR Methodology to analyze the existing knowledge in this field and explore the effects of Drones’ usage in the construction industry. Furthermore, the article has explored the benefits of using drones in construction by considering it as a project-related sector. Various dimensions of Project Management have been considered in analyzing the benefits of using Drone Technology.